2021
DOI: 10.21608/ejle.2021.82001.1022
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation in Arabic Sentiment Analysis during the Covid-19 Pandemic

Abstract: This paper classifies sentiment analysis in Arabic language and mining sentiment in relation to the COVID-19 pandemic in the period (2019 -2021). Three large data sets are collected from tweets, hotel and restaurant reviews for building the proposed sentiment analysis model. We compared eight machine learning algorithms, Multinomial Naïve Bayes (MNB), Bernoulli Naïve Bayes (BNB), Decision Tree (DT), K-nearest neighbour classifier (KNN), Support Vector Machines (SVM), Linear Support Vector Classifier (LSVC), Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As a result of the impact of such a pandemic on the education system, these nations pushed on improving broadcast teaching, virtual class infrastructures and online teaching. Sakr et al (2021). Where according to the study conducted by Aristovnik et al (2020) which undertaken nearly 30,000 sample students tweets from 62 countries analyzed using the Naive-based classifier, concluded that the lower living standard students with financial problems were not satisfied with their academic life as the pandemic affected their life more.…”
Section: Sentiment Analysis and Emotion Detection During-covidmentioning
confidence: 99%
“…As a result of the impact of such a pandemic on the education system, these nations pushed on improving broadcast teaching, virtual class infrastructures and online teaching. Sakr et al (2021). Where according to the study conducted by Aristovnik et al (2020) which undertaken nearly 30,000 sample students tweets from 62 countries analyzed using the Naive-based classifier, concluded that the lower living standard students with financial problems were not satisfied with their academic life as the pandemic affected their life more.…”
Section: Sentiment Analysis and Emotion Detection During-covidmentioning
confidence: 99%